2005
DOI: 10.1038/sj.jp.7211404
|View full text |Cite
|
Sign up to set email alerts
|

A Bedside Prediction-Scoring Model for Late-Onset Neonatal Sepsis

Abstract: OBJECTIVE:Insufficient tools for bedside prediction of late-onset neonatal sepsis (LNS) initiated this study. The objective was to develop and validate a simple prediction-scoring model for LNS defined as culture-proven sepsis occurring 72 hours after birth. METHODS:The study was performed at a university hospital in Bangkok. The derivation phase included medical records of 1870 neonates, randomly selected from 9347 records of neonates who had been hospitalized for >72 hours during 1998 to 2000, of which 1824 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 20 publications
1
39
0
Order By: Relevance
“…We found the performance of the LNS score determined by the AUC was acceptable and comparable with the internal validation study (n ¼ 73). 6 In contrast to the external validation study of the NOSEP score, 9 the AUC of the LNS score was comparable to the AUC of the original study, without any need for a modification of the LNS score. Hui et al 12 reported performance of procalcitonin testing for diagnosis of LNS in the same study population elsewhere.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…We found the performance of the LNS score determined by the AUC was acceptable and comparable with the internal validation study (n ¼ 73). 6 In contrast to the external validation study of the NOSEP score, 9 the AUC of the LNS score was comparable to the AUC of the original study, without any need for a modification of the LNS score. Hui et al 12 reported performance of procalcitonin testing for diagnosis of LNS in the same study population elsewhere.…”
Section: Discussionmentioning
confidence: 87%
“…6 The suggested cut-off value of 3 was based on test performance and the estimated probability. The observed prevalence of LNS in this study showed the same pattern of risk classified by the LNS score.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations